Respiratory effects of aflatoxin b1 and risk of workplace to home exposure among selected rice millers in Malaysia - Asri, Amiratul Aifa Mohamad (2020)
Rice milling process produces a huge amount of dust which may contain fungal toxins due to improper handling and storage at high humidity levels. Aflatoxin B1 (AFB1) is the most potent among the aflatoxins and carcinogenic to humans when ingested or inhaled that might cause hepatocellular cancer or lung cancer. This study aims to assess the exposure of AFB1 and its respiratory effects among selected rice millers in Malaysia. Area and personal dust exposure were evaluated using a sampling train consist of a glass microfibre filter, IOM sampler and GilAir Plus Personal Air Sampling Pump. The pump was worn for eight working hours, attached to the workers’ belt. Lung function test was performed pre and post-shift. The palms of both hands of the workers were swabbed with sterile cotton pads wetted with Phosphate Buffered Saline Tween-20 solution (PBST), pre and post-shift. Home dust sampling was done by vacuuming the living room using a DUSTREAM collector containing mesh nylon filter attached to a vacuum cleaner. The results were then compared with the control group involving USM administration workers. Questionnaires were given to collect information on sociodemographic data, occupational details, personal protection equipment (PPE) compliance, workplace practices, respiratory symptoms and factors that lead to take-home exposure to AFB1. Altogether, there were 115 subjects participated in the study, 77.5% of them are Malay. AFB1 was detected in 14.1% (n = 10) of personal airborne dust samples (median: 0.16, IQR: 0.14-0.90). Post-shift hand swab was positive with AFB1 in two rice millers 13.0% (n = 2) (median: 0.24 ng/ml, IQR: 0.24-0.27 ng/ml). However, AFB1 was non-detected on hand swabs among office workers (<LOQ: 0.24 ng/ml). There was no significant difference was found in post-shift lung function between rice millers and controls (FVC: p = 0.911, FEV1: p = 0.637, FEV1/FVC: p = 0.385, PEF: p = 0.160) after controlled for gender and smoking as confounders. The AFB1 home dust level among rice millers was 0.18 ng/kg (IQR: 0.08 – 8.32). There was no significant difference in AFB1 levels in home dust between both groups. To conclude, detected AFB1 at rice mills (airborne filter and hand swabs) were lower than the permissible limit (30 ng/m3). Consequently, there is no significant correlation between workplace and home AFB1 levels. Thus, the presence of AFB1 at home could be influenced by environmental factors such as human activities at home. Cumulative effects may pose risks over the years so proper control measures such as hygiene practices at work and preventing take-home exposure are highly recommended to reduce the levels of AFB1 among the workers and their family members.